Nghiên cứu ảnh hưởng của tỷ lệ các hợp phần đến phản ứng khâu mạch nhựa epoxy biến tính dầu đậu nành bằng dianhydrit piromelitic - Hiền, Lê Xuân; Mai, Đỗ Ngọc (Vietnam Journal of Chemistry, 2014)
The influence of the content of epoxy resin modified by soyabean oil (ESO), dianhydrite piromelitic (DAP) and dimethylbenzylamine (DMBA) on the crosslinking reaction of ESO by DAP has been studied and the optimal conditions for the curing have been determined. It was showed that at the optimal conditions: Equal mol of epoxy and anhydrite groups, reactions temperature and duration 120 oC and 90 min, respectively, the DMBA content of 2.31 % of the total mass of ESO and DAP, the epoxy and anhydrite groups have been totally converted, led to formation of a cured coating with gel fraction 84 %, swelling degree 160 %. Keywords: Epoxy resin, soyabean oil, dianhydrite piromelitic, curing.